Preliminary study of 50 W Class-E GaN FET amplifier for 6.78 MHz capacitive wireless power transfer - Muharam, Aam; Mostafa, Tarek Mahmoud; Ahmad, Suziana; Masuda, Mitsuru; Obara, Daiki; Hattori, Reiji; Hapid, Abdul (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2020)
A preliminary study of Class-E radio frequency power amplifier for wireless capacitive power transfer (CPT) system is presented in this paper. Due to a limitation in coupling capacitance value, a high frequency operation of switching power inverter is necessary for the CPT system. A GaN MOSFET offers reliability and performance in a high frequency operation with an improved efficiency over a silicon device. Design specification related to the parallel load parameter, LC impedance matching and experimental analysis of the amplifier is explored. An experimental setup for the proposed inverter and its integration with the CPT system is provided, and the power efficiency is investigated. As a result, by utilizing a 6.78 MHz resonant frequency and a 50 â„¦ resistive load, 50 W of power has been transmitted successfully with an end to end system efficiency over 81 %. Additionally, above 17 W wireless power transfer was demonstrated successfully in the CPT system under 6 pF coupling with the efficiency over 70 %.